Neuromodulation of Gamma-Range Auditory Steady-State Responses: A Scoping Review of Brain Stimulation Studies - Griskova-Bulanova, Inga; Sveistyte, Kristina; Bjekic, Jovana (Frontiers in Systems Neuroscience, 2020)
Neural oscillations represent a fundamental mechanism that enables coordinated action during normal brain functioning. Auditory steady-state responses (ASSRs) are used to test the ability to generate gamma-range activity. Different non-invasive brain stimulation (NIBS) techniques have the potential to modulate neural activation patterns that are aberrant in a variety of neuropsychiatric disorders. Here we summarize the current state of knowledge on how different methods of NIBS (transcranial altering current stimulation - tACS, transcranial direct current stimulation - tDCS, transcranial random noise stimulation – tRNS, paired associative stimulation - PAS, repetitive transcranial magnetic stimulation - rTMS) affect the gamma-range ASSRs in both healthy and clinical populations. We show that the current research has been far from systematic and methodologically heterogeneous. Nevertheless, some brain stimulation techniques, especially tACS and rTMS show strong potential for further exploration. We outline the main findings and provide directions for further research into neuromodulation of ASSRs as a promising biomarker of different psychopathological conditions such as schizophrenia, bipolar disorder, attention deficit hyperactivity disorder (ADHD), autism.